Status Gizi Berhubungan dengan Perkembangan Bicara Anak Usia 22 – 31 Bulan Di Desa Karampuang - Rusliana, Rusliana; Mustadiarto, Mustadiarto (Mando Care Jurnal, 2024)
Speech development in children aged 22–31 months is associated with nutritional status. Children who are malnourished can disrupt their speech development. Research objectives This research was conducted to determine factors related to speech development in early childhood. The method used in this research is a quantitative method with an observational analytical research type with a cross sectional approach. The sample used was 40 samples, the sampling technique used Random Sampling technique. The study results were measured using the Chi-Square test, with statistical analysis conducted through the SPSS application. The findings revealed that respondents with good nutritional status accounted for 27 (67.5%), while those with poor nutritional status totaled 13 (32.5%). Respondents with good speech development made up 27 (67.5%), whereas those with poor speech development totaled 13 (32.5%). The study found a correlation between nutritional status and speech development in early childhood.